Emissions of volatile organic compounds (VOCs) from gasoline- and liquified natural gas (LNG)-fueled vehicles in tunnel studies. (1st August 2020) - Song, Congbo; Liu, Yan; Sun, Luna; Zhang, Qijun; Mao, Hongjun
Abstract: Gasoline vehicles (GVs) emissions generally dominate ambient volatile organic compounds (VOCs) in urban areas, while VOC emissions from liquefied natural gas (LNG)-fueled vehicles play an increasingly important role in urban air quality, due to fuel transition from gasoline/diesel to alternative fuels. Here, an extensive dataset of VOC samples collected in three urban tunnels in China was used to explore real-world emission characteristics of ninety-nine VOC species from both GVs and LNG-fueled vehicles. The fleets in the Beijing and Tianjin tunnels comprised > 94% GVs whereas the fleet in the Nanjing tunnel comprised both GVs ( ∼ 87%) and LNG-buses ( ∼ 13%). The VOC emission factors (EFs) in the Beijing tunnel and Tianjin tunnel were highly correlated, implying that they can be applied as existing emission datasets from GVs with aim of distinguishing emissions from LNG-fueled vehicles and GVs in the Nanjing tunnel. For fleet emissions, the average VOC EFs have declined substantially over the last decade; the relative compositions of benzene, toluene, and ethylbenzene were quite stable despite differences in fleet composition. Ethylene, isopentane, ethane, and toluene; and ethane and propane were enriched in VOC emissions ( v ∕ v ) from GVs and LNG-fueled vehicles, respectively. Methyl t e r t -butyl ether, 2, 2, 4-trimethylpentane, 2, 3, 4-trimethylpentane, 3-methylpentane, and methylcyclopentane were potential VOC tracers for GVs. Ethane, propane, and 2, 3-dimethylbutane were key tracers that distinguished LNG-fueled vehicles from GVs. Propane, isobutane, and n-butane were key VOC tracers that distinguished liquefied petroleum gas-fueled vehicles from GVs. Alkanes dominated fleet emissions both by mass and by volume. However, aromatics and alkenes (mainly ethylene and propylene) dominated VOC reactivity from gasoline- and LNG-fueled vehicles, respectively. Our study highlights that the wide discrepancy in fleet VOC emissions could be attributed to fleet compositions. Highlights: Inconsistent fleet-average VOC emissions due to different fleet compositions. Real-world VOC emissions from gasoline vehicles (GVs) were measured in two tunnels with >94% GVs in the fleets. Constrained linear regression was used to distinguish VOC emissions from LNG-fueled vehicles and GVs. Fleet-average emission factors of VOCs substantially decreased over the last decade. Aromatics and alkenes dominated VOC reactivity from gasoline- and LNG-fueled vehicles, respectively.